Epidemiological trends of lung cancer attributed to residential radon exposure at global, regional, and national level: a trend analysis study from 1990 to 2021 - Qiang Xiong; Qiang Xiong; Zhen Zhang; Zhen Zhang; Jianliang Peng; Jianliang Peng; Jing Liang; Jing Liang; Dexing Lian; Dexing Lian; Xipeng Zhao; Xipeng Zhao; et al. (Frontiers in Public Health)
BackgroundLung cancer (LC) remains a leading cause of cancer-related mortality globally, with radon identified as the second major risk factor. This study aimed to analyze the global, regional, and national burden of LC attributed to residential radon exposure from 1990 to 2021.MethodsThe Global Burden of Disease (GBD) 2021 database were employed to estimate the disease trends of LC attributed to residential radon exposure across sex, age groups, and socioeconomic development levels via the socio-demographic index (SDI). Trends of the age-standardized rates (ASRs) were evaluated using estimated annual percentage change (EAPC). The relationship of the socio-demographic index (SDI) with ASRs was assessed via Spearman correlation and LOESS regression.ResultsIn 2021, residential radon caused 82,160 global LC deaths (an increase of 66.87% since 1990), while the ASRs declined globally (ASMR EAPC: −0.26, 95%C: −0.51 to −0.01; ASDR EAPC: −0.65, 95%CI: −0.85 to −0.44). The disease burden of residential radon-induced LC was higher in middle and high latitude nations. With the increase of SDI, ASRs showed a downward trend in most regions, while an upward trend at national level. Across age and sex, the older adult males exhibited higher burden.ConclusionWhile global ASRs declined, rising absolute burdens underscore radon’s persistent threat, particularly in rapidly urbanizing and high-latitude regions. Targeted radon mitigation, enhanced early detection, and gender-specific interventions are critical.